Edukacja obronna w systemie bezpieczeństwa państwa .......... 71 - Drzewiecki, Andrzej (Systemy bezpieczeństwa: Wymiar lokalny i państwowy, 2020)
The article poses the results of research focused on the channels of international exchange of criminal information used by the Polish Police. Particular attention was paid to such cooperation tools as: I-24/7 (Interpol), SIENA (Europol), as well as exchange of information between SIRENE bureaus. The outcome of the research carried out during the preparation of the article allowed to show the Polish Police as an element of the global security system providing each other with information necessary to effectively fight against international crime and terrorism.